Empty chair therapy untuk menurunkan gejala depresi pada remaja korban perundungan - Anindyah Sekarini; Siti Muthia Dinni (Universitas Muhammadiyah Malang, 2023)
Depression is a disorder that leads to a more negative mood. The subject shows symptoms of depressive disorder in the form of depression affect, lost interest in doing activities or hobies and increased hypersomnia. Subject was an 15-year-old woman who had experienced as victims of bullying. The purpose of this case study is to reduce depressive symptoms through the empty chair. There are feelings of guilt and worthlessness, trouble concentrating to complete the school task, and looking future improperly. The assessment method were used interview, observation, psychological test, and BDI (Beck Depression Inventory). The intervention used in this case was Gestalt Therapy with Empty Chair Technique. Intervention target to decreased depression symptoms and helps subject to live well everyday. The results of the intervention showed that empty chair therapy effective in reducing depression symptoms in subject. There was decreased BDI score from 37 to 22. Depresi adalah gangguan yang mengarah ke suasana hati yang lebih negatif. Subyek menunjukkan gejala gangguan depresi berupa afek depresi, kehilangan minat dalam melakukan aktivitas atau hobi dan peningkatan hipersomnia. Subjek adalah seorang wanita berusia 15 tahun yang pernah mengalami sebagai korban bullying. Tujuan dari studi kasus ini adalah untuk mengurangi gejala depresi melalui kursi kosong. Ada perasaan bersalah dan tidak berharga, sulit berkonsentrasi untuk menyelesaikan tugas sekolah, dan memandang masa depan dengan tidak tepat. Metode penilaian yang digunakan adalah wawancara, observasi, tes psikologi, dan BDI (Beck Depression Inventory). Intervensi yang digunakan dalam kasus ini adalah Terapi Gestalt dengan Teknik Kursi Kosong. Target intervensi untuk mengurangi gejala depresi dan membantu subjek untuk hidup dengan baik setiap hari. Hasil intervensi menunjukkan bahwa terapi kursi kosong efektif dalam mengurangi gejala depresi pada subjek. Terjadi penurunan skor BDI dari 37 menjadi 22.